PENGEMBANGAN APLIKASI PENYEDERHANAAN ALJABAR BOOLEAN DALAM BENTUK SUM-OF-PRODUCT DENGAN MENGGUNAKAN METODE QUINE MCCLUSKEY - Wamiliana, Wamiliana; Zahroh, Shara Siti; Wulandari, Ossy Dwi Endah (Jurnal Komputasi, 2013)
This study implements the Quine McCluskey method to minimize the Boolean function. There are several methods can be used in the minimization of Boolean functions. Afrisal [1] conducted a study to apply the Karnaugh Map method. Tomaszewski [4] applied the Quine McCluskey method to make program to simplify Boolean Algebra with a maximum input function at most 4 variables which are initialized before. In this study, the Quine McCluskey implemented in the program and it can simplify the input function with a maximum length of 26 variables. That input can be entered directly via keyboard.Keywords: efficiency; minimization of Boolean Algebra; Quine McCluskey method.